(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyse the influence of liquidity, profitability, leverage, and Corporate Social Responsibility (CSR) on firm value in the healthcare sector listed on the Indonesia Stock Exchange for the period 2021–2023. Enterprise value is proxied using Tobin’s Q, whilst liquidity is measured by the Current Ratio (CR), profitability by Return on Assets (ROA), and leverage by the Debt-to-Equity Ratio (DER). This study employs a quantitative approach using purposive sampling, yielding 114 observations from 38 companies. The data were analysed using multiple linear regression with the aid of SPSS, beginning with descriptive statistics, classical assumption tests, and hypothesis testing. The results indicate that, simultaneously, the variables of liquidity, profitability, leverage, and CSR influence firm value. Partially, profitability has a significant positive effect on firm value, whilst liquidity, leverage, and CSR show varying results and are not entirely significant. These findings indicate that a firm’s ability to generate profits is a key factor considered by investors when evaluating firms, particularly in the healthcare sector amidst the post-pandemic dynamics.